An enhancement of the application for fast track arbitration in the Malaysian construction industry / Nur Khodijah Muhammad Fadhlullah Ng - Muhammad Fadhlullah Ng, Nur Khodijah (2020)
The increase number of construction disputes in the last few decades has marked the important role of the construction industry. Arbitration has become continuously popular and strengthened its position to settle within stipulated time compare to litigation. However, the arbitral process takes longer time, which leads to fast track arbitration. Due to the weaknesses of traditional arbitration process, the use of fast track arbitration is seen as an efficient approach in resolving construction disputes, as part of the strategy to limit conflict between the contracting parties. However, the utilisation of fast track arbitration in the Malaysian construction industry is low compared to United Kingdom, France, Singapore and Hong Kong. Therefore, this research aims to establish the enhance application of fast track arbitration in the Malaysian construction industry with the support of three objectives. The objectives are to identify the issues on existing fast track arbitration in the Malaysian construction industry; to explore the application of fast track arbitration in the Malaysian construction industry and to establish recommendations to further enhance the application of fast track arbitration in the Malaysian construction industry. Hence, the qualitative approach was adopted. This research executed semi – structured interviews to twenty (20) construction arbitrators to meet the aim of the research. The collected data was analysed with CAQDAS (Computer Assisted Qualitative Data Analysis Software), Atlas.ti Version 8 through the process of content analysis and thematic analysis. It can be summarised that the fast track arbitration process offers by the arbitral institution is inadequate in terms of competency to meet the increased number of the construction disputes. Besides, by viewing on its application, the fast track arbitration has found ineffective in terms of its application due to lack of enforcement from the responsible parties. Thus, this research is intended to develop enhanced application of the fast track arbitration through the role of arbitral institution. By adopting this approach, the role of arbitral institution as the body that responsible to manage construction disputes could be relied upon. As the responsible body has clear procedure, the adoption of fast track arbitration in construction disputes by the arbitrators shall be effective in this sense. Apart from that, awareness of the existing fast track arbitration is another crucial issue that requires attention. Combination roles of the arbitral institution and the arbitrators could assist in determining preferable seat of the arbitration proceedings. As a conclusion, the outcome of this research is essential in ensuring the quality improvement of Alternative Dispute Resolution (ADR) in Malaysia.